If it's not what You are looking for type in the equation solver your own equation and let us solve it.
D( y )
y = 0
y = 0
y = 0
y in (-oo:0) U (0:+oo)
2/5 = y-(6/y)+3 // - y-(6/y)+3
6/y-y+2/5-3 = 0
6*y^-1-1*y^1-13/5*y^0 = 0
(6*y^0-1*y^2-13/5*y^1)/(y^1) = 0 // * y^2
y^1*(6*y^0-1*y^2-13/5*y^1) = 0
y^1
(-13/5)*y-y^2+6 = 0
(-13/5)*y-y^2+6 = 0
DELTA = (-13/5)^2-(-1*4*6)
DELTA = 769/25
DELTA > 0
y = ((769/25)^(1/2)-(-13/5))/(-1*2) or y = (-(-13/5)-(769/25)^(1/2))/(-1*2)
y = ((769/25)^(1/2)+13/5)/(-2) or y = (13/5-(769/25)^(1/2))/(-2)
y in { ((769/25)^(1/2)+13/5)/(-2), (13/5-(769/25)^(1/2))/(-2)}
y in { ((769/25)^(1/2)+13/5)/(-2), (13/5-(769/25)^(1/2))/(-2) }
| g-5/6=-8 | | -3/5y=-50 | | c/4=9/3 | | 26/49*35/44*8/65 | | 26/49*35/44*65 | | Y=5+12x | | 6b+7=-2b+23 | | 3/5x-7=17 | | 3/4n=30 | | -17+1x=11 | | 8x-4x+3x=28 | | 7/8+1/6 | | 4/5x=-20 | | -17+1x=9 | | 2/17x=8 | | (100-4x)/(3)=(5x+6)/(4)+6 | | r-1/2=-3/4 | | 5(x-3)=-2(x-3) | | 1,5(x-4)-(3-2x)=50-0,5x-(4-5x) | | y+10=-28 | | 8n-2=4+2n | | 100-4u/3=(5u+6/4)+6 | | 30x-25+20x=15-10x+5 | | 9x+7x=32 | | x^3-4x^2+14X+39=0 | | X+3=4x+18 | | -1=8+(-19) | | y-19/y=-60 | | y-2=-2 | | 9s+20=-16 | | 12/20=x/35 | | 8/x+240 |